Interval Colorectal Cancer Incidence Among Subjects Undergoing Multiple Rounds of Fecal Immunochemical Testing - van der Vlugt, M.; Grobbee, E.; Bossuyt, P.; Bos, A.; Bongers, E.; Spijker, W.; Kuipers, E.; Lansdorp_Vogelaar, Iris; Spaander, M.; Dekker, E. (W.B. Saunders Co., 2017)
© 2017 AGA Institute Background & Aims Among subjects screened for colorectal cancer (CRC) by the guaiac fecal occult blood test, interval cancers develop in 48% to 55% of the subjects. Data are limited on how many persons screened by fecal immunochemical tests (FIT), over multiple rounds, develop interval cancers. In the Netherlands, a pilot FIT-based biennial CRC screening program was conducted between 2006 and 2014. We collected and analyzed data from the program on CRCs detected during screening (SD-CRC) and CRCs not detected within the screening program (non–SD-CRC; such as FIT interval cancers, colonoscopy interval cancers, and cancer in nonparticipants). Methods Screenees with a negative FIT result received a letter explaining that no blood had been detected in the stool sample and were re-invited, if eligible, for screening biennially. Screenees with a positive FIT result (hemoglobin concentration of 10 µg Hb/g feces) were invited for consultation and scheduled for colonoscopy; results were collected. After the fourth round of FIT screening, the cohort was linked to the Netherlands Cancer Registry, through March 31, 2015; participant characteristics, data on tumor stage, location (at time of resection), and survival status were collected for all identified CRC cases. A reference group comprised all persons with CRC diagnosed in the Netherlands general population during the same period, in the same age range (50–76 years), who had not been offered CRC screening. The median time between invitations (2.37 years) was used as a cutoff to categorize participants within the FIT interval cancer category. We compared participant characteristics, tumor characteristics, and mortality among subjects with SD-CRC and with non–SD-CRC. Results A total of 27,304 eligible individuals were invited for FIT screening, of whom 18,716 (69%) participated at least once. Of these, 3005 (16%) had a positive result from the FIT in 1 of the 4 screening rounds. In total, CRC was detected in 261 participants: 116 SD-CRCs and 145 non–SD-CRCs (27 FIT interval cancers, 9 colonoscopy interval cancers, and 109 CRCs in nonparticipants). The FIT interval cancer proportion after 3 completed screening rounds was 23%. Participants with SD-CRC had more early-stage tumors than participants with non–SD-CRCs (P < .001). Of persons with SD-CRC and FIT interval cancers, significantly higher proportions survived (89% and 81%, respectively) compared with persons with colonoscopy interval cancers (44% survival) and nonparticipants with CRC (60% survival) (P < .001). Conclusions In an analysis of data from a pilot FIT-based biennial screening program, we found that among persons screened by FIT, 23% developed FIT interval cancer. FIT therefore detects CRC with 77% sensitivity. The proportion of FIT interval cancers in FIT screening appears to be lower than that with guaiac fecal occult blood testing. Clinical trial registry: yes, www.trialregister.nl, trial number: NTR5385.